2017
DOI: 10.1057/s41289-016-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Shared space streets: design, user perception and performance

Abstract: Shared space is becoming an increasingly well-accepted approach to street design, pursuing the improvement of the uses of the street on foot without restricting other modes of movement. This approach introduces some degree of uncertainty about the application of the traffic rules by minimising traffic signs and conventional physical demarcations in order to enable the different users to share the road space and negotiate their movement through and across. Despite existing evidence on reducing traffic accidents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…But while mixed lanes bear some similarity with shared space schemes, there are fundamental differences, in that the former essentially ''force'' pedestrians to share some of the space with vehicle traffic, while the latter are designed to encourage them to do so. It can be, therefore, anticipated, in line with related findings in the field so far (e.g., 24,25) that shared space features will have a positive contribution to PLOS ratings.…”
Section: Introductionsupporting
confidence: 82%
“…But while mixed lanes bear some similarity with shared space schemes, there are fundamental differences, in that the former essentially ''force'' pedestrians to share some of the space with vehicle traffic, while the latter are designed to encourage them to do so. It can be, therefore, anticipated, in line with related findings in the field so far (e.g., 24,25) that shared space features will have a positive contribution to PLOS ratings.…”
Section: Introductionsupporting
confidence: 82%
“…Since comparable before-after street scenarios are desirable but hard to achieve in reality for preference studies (Ruiz-Apilánez et al, 2017), this study used VR for environmental representation. It was conceived to allow free movement of participants inside the presented virtual environment and provide real-time aura-visualisation.…”
Section: Virtual Realitymentioning
confidence: 99%
“…Shared-street design has been applied in busy urban areas in many cities (e.g., Jaffe, 2015;Shared Space, 2005;Vasisht & Karndacharuk, 2016). It has been shown that shared streets have higher levels of safety and comfort (Ruiz-Apilánez et al, 2017;Vasisht & Karndacharuk, 2016), yet efficiencies for mobility and access, even of motor vehicles, are still maintained (Hamilton-Baillie & Jones, 2005;Karndacharuk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the negative impacts of transportation development on urban spaces and healthy behavior, it is generally accepted that an integrated design of Transport Infrastructure and Public Space (TIPS) systems is needed (Cervero, 2009;Ravazzoli and Torricelli, 2017). In this regard, considerable research have been conducted in terms of Integrated Land Use Transportation planning (Bertolini et al, 2005;Maoh and Kanaroglou, 2009), Shared Space practices (Ruiz-Apilánez et al, 2017), and developing urban design methods for drafting and evaluating transport-spaces plan scenarios (Moughtin, 2003;Van Dam et al, 2014). In order to build a holistic and sustainable TIPS environment, scholars have advocated engaging public participation and multi-disciplinary cooperation into the urban design process which includes site analysis, design procedure, plan assessment stage, and decision-making (Nieuwenhuijsen et al, 2017;Yigitcanlar and Kamruzzaman, 2014;Zhang et al, 2018).…”
Section: Urban Design Issuesmentioning
confidence: 99%